Injectable supramolecular polymer-nanoparticle hydrogels enhance human mesenchymal stem cell delivery - Abigail K. Grosskopf; Gillie A. Roth; Anton A. A. Smith; Emily C. Gale; Hector Lopez Hernandez; Eric A. Appel (Wiley, 2020)
Abstract Stem cell therapies have emerged as promising treatments for injuries and diseases in regenerative medicine. Yet, delivering stem cells therapeutically can be complicated by invasive administration techniques, heterogeneity in the injection media, and/or poor cell retention at the injection site. Despite these issues, traditional administration protocols using bolus injections in a saline solution or surgical implants of cell‐laden hydrogels have highlighted the promise of cell administration as a treatment strategy. To address these limitations, we have designed an injectable polymer-nanoparticle (PNP) hydrogel platform exploiting multivalent, noncovalent interactions between modified biopolymers and biodegradable nanoparticles for encapsulation and delivery of human mesenchymal stem cells (hMSCs). hMSC‐based therapies have shown promise due to their broad differentiation capacities and production of therapeutic paracrine signaling molecules. In this work, the fundamental hydrogel mechanical properties that enhance hMSC delivery processes are elucidated using basic in vitro models. Further, in vivo studies in immunocompetent mice reveal that PNP hydrogels enhance hMSC retention at the injection site and retain administered hMSCs locally for upwards of 2 weeks. Through both in vitro and in vivo experiments, we demonstrate a novel scalable, synthetic, and biodegradable hydrogel system that overcomes current limitations and enables effective cell delivery.